The Influence of Intellectual Intelligence, Emotional Intelligence, and Lifestyle on Financial Literacy and Financial Management Ability of Students of Panca Budi Development University - Dastin Syafitri; Noni Ardian; Cahyo Pramono (CV. Doki Course and Training, 2026)
Financial literacy and financial management skills are important competencies that students must have to face the complexity of digital financial services and economic challenges in the modern era. Lifestyle changes when studying in the city often lead to uncontrolled consumptive behavior, coupled with easy access to various digital financial services such as paylater, e-wallets, and online loans that have the potential to be abused. This study aims to analyze and test the influence of Intellectual Intelligence, Emotional Intelligence, and Lifestyle on Financial Literacy and Financial Management Ability of Panca Budi Development University students. The population in this study is all students of the Financial Management Study Program class of 2022 totaling 71 respondents using saturated sampling techniques. The data analysis method used is Partial Least Square-Structural Equation Modeling (PLS-SEM) to test the causal relationship between variables. The results of the study show that Intellectual Intelligence has a positive and significant effect on Financial Literacy and Financial Management Ability. Emotional Intelligence shows a negative influence on Financial Literacy but has a positive effect on Financial Management Ability. Lifestyle proved to be the strongest predictor that had a positive and significant effect on both dependent variables, with the most dominant influence on Financial Literacy. This research model has good predictive ability in explaining the variation in Financial Literacy and Student Financial Management Ability.